To Vote or Not To Vote: Marketing Factors Influencing the Voting Intention of University Students in Johannesburg - Morar, Anjali; ., Tinashe Chuchu (Journal of Economics and Behavioral Studies, 2015)
Voting intention has become an issue of concern worldwide with regard to successful political elections. With only 6% of South Africa’s youth having registered to vote in the 2014 elections, it is of vital importance to get a better understanding of the main reasons behind these statistics and factors that have influenced voting intentions. Although several studies have explored this area of research, it remains a topic of interest. This research paper aims to examine the factors behind voting intention of the youth in South Africa, as most are in their first or second democratic election. This study adds to existing literature on political parties as brands and factors influencing the youth’s intention to vote. These factors include advertising mediums, convenience factors of location and registration, and social pressures from peers or family on voting intention. By means of quantitative research, two hundred and fifty questionnaires were distributed amongst students from the University of Witwatersrand. The findings indicate that five of the six hypotheses are insignificant with the exception of radio advertising. The results of this study provide political parties with a better understanding of the factors that prove to be ineffective when targeting Generation Y consumers in South Africa. It further provides political parties with an opportunity to more successfully reach such individuals through other media platforms.